La nutrición infantil para fortalecer el aprendizaje en los niños de 4 a 5 años de la unidad educativa Fernando Suárez palacio de la ciudad de Loja, periodo 2017-2018 - Quizhpe Armijos, Jenniffer Valeria (2018)
The thesis entitled "CHILD NUTRITION TO STRENGTHEN LEARNING IN CHILDREN FROM 4 TO 5 YEARS OF THE EDUCATIONAL UNIT FERNANDO SUÁREZ PALACIO DE LA CIUDAD DE LOJA, PERIOD 2017-2018". Its general objective is to: Determine the incidence of nutrition in learning in children from 4 to 5 years. The methods that were used were: scientific, analytical - synthetic, deductive and statistical; In the same way, for the obtaining of information, different techniques were used as a survey directed to a sample of 15 parents to know about the feeding in the home; and the "REAA" adaptation of basic functions test applied to 15 children to determine learning. From the application of the survey it is obtained that 73% of parents do not know what is an adequate nutrition for the development of the child; 67% send daily sweets in the lunch box therefore, the school lunch does not meet the necessary nutritional requirements and this has as a consequence children with little predisposition to the activities proposed by the teacher, showing the lack of information and nutritional habits in the families of the students; On the other hand, the application of pre-test in general was obtained 53% of children had a low level of learning, after the application of the proposal in the post-test an advance in learning was reached with 80% of children with a medium and good mastery in the areas of learning, so it is concluded that it is necessary to eat nutrient-rich foods such as: fruits, vegetables, vegetables to optimize a comprehensive development and avoid later problems such as malnourished children, Obese, prone to illnesses, their physical condition being affected, thus harming their academic performance and this has as a consequence children with little predisposition to the activities proposed by the teacher. Finally, it is recommended to provide varied foods at the appropriate times, inculcating avoiding excess in the consumption of sweets, so that in this way your body receives carbohydrates, proteins, vitamins, minerals and enough water.